The dialectics of citizenship : exploring privilege, exclusion and racialization - Reiter, Bernd, 1968- (Michigan State University Press, 2013)
What does it mean to be a citizen? What impact does an active democracy have on its citizenry and why does it fail or succeed in fulfilling its promises? Most modern democracies seem unable to deliver the goods that citizens expect; many politicians seem to have given up on representing the wants and needs of those who elected them and are keener on representing themselves and their financial backers. What will it take to bring democracy back to its original promise of rule by the people? Bernd Reiter's timely analysis reaches back to ancient Greece and the Roman Republic in search of answers.